Reaction of Winter Cover Crops to Meloidogyne enterolobii and Glasshouse Bioassay for Evaluating Utility in Managing M. enterolobii in Soybeans - Saha Neel; Schwarz Tanner; Mowery Samantha; Gorny Adrienne M. (Journal of Nematology, 2023)
Meloidogyne enterolobii is an invasive and highly aggressive root-knot nematode pathogen impacting the Southeastern United States. Winter cover cropping may be a cost-effective method for reducing populations of M. enterolobii in between summer cash crops, yet a gap in the knowledge remains about the response of these cover crops to M. enterolobii and their utility in suppressing nematode populations prior to a cash crop. A “two-step” glasshouse bioassay was performed to evaluate eight winter cover crops popular in North Carolina for their direct response to M. enterolobii infection, and to quantify their effect in reducing nematode populations for the following soybean plants. Data on cover crop root galling, soybean root galling, soybean shoot fresh weight, soybean root fresh weight, eggs per gram of soybean root, and a modified reproductive factor were collected. Cereal cover crops did not display root galling, and there was significantly less root galling in those soybean plants following cereal winter cover crops when compared to those following broadleaf winter cover crops. Broadleaf winter cover crops resulted in significantly higher eggs per gram of soybean root and modified reproductive factor in the soybean plants, compared to cereal cover crops and non-inoculated controls. Results from this study suggest that cereal winter cover crops may be poor-hosts to M. enterolobii and may significantly reduce M. enterolobii populations before a soybean crop, compared to broadleaf winter cover crops. This study lays the groundwork for management recommendations and future field trials to assess management of M. enterolobii through winter cover cropping.